Medicine shortages – A study of community pharmacies in Finland. Issue 2 (February 2015) - Heiskanen, K.; Ahonen, R.; Karttunen, P.; Kanerva, R.; Timonen, J.
Highlights Medicine shortages are common in community pharmacies. Medicines in short supply are very commonly used medicines. The reasons behind the medicine shortages are rarely reported to the pharmacy. Medicine shortages cause problems for the pharmacies in every third case. Shortages cause customer dissatisfaction and increase workload of the pharmacy.